Bear in a square - Blackstone, Stella (Barefoot Books Bristol, 1998)
Share the adventure of a big, friendly bear as he roams through all sorts of crazy settings, discovering different shapes along the way. The book is designed to offer young children practice in both counting and shape recognition.